Stress and coping: An economic approach - Klaus Wälde (Friedrich Schiller University Jena, 2015)
Stress is ubiquitous in society. In our model, stressors translate into subjective stress via an appraisal process. Stress reduces instantaneous utility of an individual directly and via a cognitive load argument. Coping can be functional and under the control of the individual or more automatic with dysfunctional features. We predict the occurrence and frequency of uncontrolled coping - emotional outbursts - as a function of an individuals personality and environment. Outbursts cannot always be avoided. Delaying emotional outbursts artificially can lead to even more outbursts. Looking at the effect of psychotherapy shows that expecting little and being emotional can help maximizing well-being.
Keywords: D03; D91; I12; 330; controlled vs. automatic reaction; coping; emotional outbursts; optimal stopping problem; personality; stress